2015
DOI: 10.1371/journal.pone.0129040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mutation in the Thyroid Stimulating Hormone Receptor (TSHR) on Development, Behaviour and TH Levels in Domesticated Chickens

Abstract: The thyroid stimulating hormone receptor (TSHR) has been suggested to be a “domestication locus” in the chicken, due to a strong selective sweep over the gene found in domesticated chickens, differentiating them from their wild ancestor the Red Junglefowl (RJF). We investigated the effect of the mutation on development (incubation time), behaviour and thyroid hormone levels in intercross chickens homozygous for the mutation (d/d), wild type homozygotes (w/w) or heterozygotes (d/w). This allowed an assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…In previous experiments, we have shown that the TSHR-mutation also affects other aspects of chicken biology (Karlsson et al, 2015). For example the d/d genotype showed a longer incubation time, less fearful behaviours, lower aggression, and decreased levels of the thyroid hormone T4, in comparison to the w/w genotype.…”
Section: Wl (All D/d) Photoperiodic Regulation Of Dio2 and Dio3mentioning
confidence: 92%
See 2 more Smart Citations
“…In previous experiments, we have shown that the TSHR-mutation also affects other aspects of chicken biology (Karlsson et al, 2015). For example the d/d genotype showed a longer incubation time, less fearful behaviours, lower aggression, and decreased levels of the thyroid hormone T4, in comparison to the w/w genotype.…”
Section: Wl (All D/d) Photoperiodic Regulation Of Dio2 and Dio3mentioning
confidence: 92%
“…In previous studies, we have shown that the mutation delays hatching by about one day, and also modifies a range of behavior in a way typically associated with domestication (Karlsson et al, 2015). In the present study we focus on the effect on photoperiodic responses.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been shown that a mutation in the TSHR genes in chickens can alter photoperiod response, with reduced seasonality of reproduction, and more frequent egg production (Karlsson et al, 2015(Karlsson et al, , 2016. The mutation is fixed in the domestic breed, the White Leghorn chicken, and not found (at least in high frequency) in the ancestral strain, Red Jungle Fowl.…”
Section: Current Status Of the Two Hypotheses In Light Of The Genomimentioning
confidence: 99%
“…These findings are supported by zooarchaeological assemblages from England and Germany, spanning the medieval period, which show an increase in both the overall frequency of chickens and the relative proportion of adult hens-interpreted as sign of increased egg production (Serjeantson 2006;Sykes 2007;Holmes 2014). Functional genetic investigation of the pleiotropic effects of the TSHR derived allele in chickens has shown that it is associated with increased egg production (Karlsson et al 2016), decreased aggression and less fearful behaviours (Karlsson et al 2015)-consistent with artificial selection for intensified egg production during the Medieval period. Evidently, TSHR has played an important role in the evolutionary history of domestic chickens, however, its identification as a domestication locus is erroneous and it can better be described as an improvement trait.…”
Section: Temporal Pattern Of Genetic and Morphological Changesmentioning
confidence: 79%